Ներսես Լամբրոնացու՝ Աստվածամոր վերափոխմանը նվիրված ներբողի բնագրային և լեզվաոճական քննություն - Ավետիսյան, Արփինե
Archbishop Nerses Lambronats‘i is one of the outstanding medieval authors and Fathers of the Armenian Church. He was a poet, prose writer, translator, and commentator (he wrote commentaries on Genesis, Ecclesiastes, Wisdom, he inter-preted church rites, the mystery of the Liturgy etc.). His panegyric on the Assumption of Virgin Mary was published on the basis of one manuscript (Vienna, No. 610, 1788) as a prose text, but it clearly has a rhythm and sometimes rhymes, which allowed us to break it into verses. Our critical edition of this panegyric is based on four manuscripts of Matenadaran, the oldest surviving manuscript from the Church of the Forty Martyrs in Aleppo, and the previous edition. Lambronats‘i has applied various means of expression in his panegyric: epi-thets, comparisons, metaphors, repetitions etc., which have created his original viv-id and eloquent style. Архиепископ Нерсес Ламбронаци – один из выдающихся отцов Армянской Церкви и величайших средневековых писателей. Он был поэтом, прозаиком и переводчиком, а также талантливым толкователем Священного Писания. Известны его толкования на книги Бытия, Экклезиаст, Премудрости, размышления о церковных обрядах и толкование тайны Литургии и т.д.. Его ода, посвященная Вознесению Девы Марии, была опубликована по одной поздней рукописи (Вена N 610, 1788 г.) в виде прозаического текста. Однако в ней четко заметны ритм, а местами и рифма, что позволило нам разделить ее на стихотворные строки. Нами издан критический текст этой оды, с использованием четырех рукописей Матенадарана имени Маштоца, древнейшей сохранившейся рукописи из церкви Сорока мучеников в Алеппо и текста начальной публикации.
Keywords: Ձեռագրեր; Կրոնական տոներ